Design of a callback system for computer scraps in Thailand - Kamnerdwam, Apichon; Sinthavalai, Runchana; Rattanamanee, Wanida; Suntiamorntut, Wannarat (Asia-Pacific Journal of Science and Technology, 2017)
Nowadays, the quantity of end-of-life computer or computer scraps in Thailand has increased continuously. In addition, Thailand is also still lacking of the collection system to recycle with an efficiently recycling process, which it affects to human, environment and low potentially recycling process. Hence, this research aims to investigate and design a callback system for computer scraps in Thailand. This research consists of the study of current problem and management, the study of strategy and solution, reverse logistics network design, and analysis of the strategy in callback system. The results showed that the designed callback system consists of six parts; source of scraps, callback point, callback center, collection center, recycling plant, and material market. There are used as components in the strategy of a callback system for recycling with the 3Rs & EPR principle and WEEE & RoHS regulation. This designed system can be managed and controlled by the public sector, private sector, or both.